Genetic and phenotypic characterisation of commercial dusky kob (Argyrosomus japonicus) cohorts - Jenkins, Stephan Francois (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.